Marriage Satisfaction among Civil Servants in Provincial Government: The Role of Adult Attachment and Religiosity - Rumondang JK Napitu; Yuspendi Yuspendi; Rosida Tiurma Manurung (Kuras Institute, 2023)
Marriage is a beneficial institution when it provides satisfaction to both partners. However, divorce rates have increased in Indonesia in the past five years, with Riau Province ranking eighth in the country with the highest divorce rate. This study aimed to investigate the extent to which adult attachment and religiosity influence the marital satisfaction of civil servants in Riau Province. Adult attachment dimensions were assessed using the Experience in Close Relationship (ECR) Scale Inventory, while religiosity was measured using The Four Basic Dimensions of Religiousness Scale (4-BDRS). Marital satisfaction was evaluated using the Marital Satisfaction Scale (MSS), which was adapted from the Marital Satisfaction Synder Inventory. The sample comprised 350 participants who met the eligibility criteria, selected using offline and online surveys through convenience sampling. The results of the multiple regression analysis revealed that the anxiety and avoidance dimensions of adult attachment, along with religiosity, jointly influenced the marital satisfaction of civil servants in the Riau Province government, accounting for 52.6% of the variance. The analysis also showed that the avoidance dimension of adult attachment had a more significant effect on marital satisfaction than the anxiety and religiosity dimensions. This study provides important information for the government to improve the marital satisfaction of civil servants in different regions of Indonesia.